Analisis Tingkat Kepuasan Kerja Berdasarkan Faktor Budaya Organisasi dan Lingkungan Kerja Guru (Studi pada MAN Se-Kabupaten Bireuen - Aceh) - Raihan, Iskandar; Neni, Karno; Tawakal, Tawakal (peusangan, 2024)
This research aims to determine and quantitatively describe the level of job satisfaction based on organizational culture and teacher work environment factors, with a case study of teachers in MAN in Bireuen Regency, Aceh province. The research sample was 65 teachers, with data collection through closed questionnaires. Analysis using a path model approach. The results of the research concluded that school organizational culture and work environment contributed to increasing job satisfaction for State MA teachers in Bireuen district, respectively by 25.28% and 20.68%. And the simultaneous contribution of organizational culture and work environment to teacher job satisfaction is 37.24%.